Clinical Characteristics of Hypertensive Patients with Obstructive Sleep Apnoea Syndrome Developing Different Types of Left Ventricular Geometry. (25th January 2021) - Myslinski, Wojciech; Rekas-Wojcik, Agata; Dybala, Andrzej; Zakrzewski, Maciej; Barud, Wojciech; Prystupa, Andrzej; Dzida, Grzegorz; Bryl, Wiesław; Mosiewicz, Jerzy
Abstract : Objective . The objective of the study was to compare polygraphic parameters and selected laboratory parameters in patients with obstructive sleep apnoea (OSA) who develop various types of left ventricular (LV) geometry. Material and Methods . The research covered 122 patients with obstructive sleep apnoea and coexisting effectively treated systemic hypertension (95 men, 27 women, average age: 54 ± 10.63 ). Overnight polygraphy, echocardiography, carotid artery ultrasonography, and laboratory measurements were performed. The patients were classified into four groups, depending on LV geometry. Group 1 comprised patients with normal LV geometry, group 2 included those with LV concentric remodelling. Group 3 and group 4 were patients with LV hypertrophy, concentric or eccentric, respectively. Results . The most frequent type of LV geometry in the examined population was eccentric hypertrophy (36%). The highest average values of BMI and T-Ch were observed in the group of patients with concentric remodelling (group 2). The most severe respiratory disorders were found in the group of patients developing LV concentric hypertrophy (group 3); however, these differences were not statistically significant in comparison to other groups. Patients with LV eccentric hypertrophy had significantly decreased LV ejection fraction (p = 0.0008 ). Conclusions . LV eccentric hypertrophy is the most frequent type of LV geometry in OSA patients. Patients with severe sleep-disordered breathing are more likely to develop concentric hypertrophy, while concentric remodelling occurs more frequently among OSA patients with other coexisting conditions, such as obesity or lipid-related disorders.